1999
DOI: 10.1080/00480169.1999.36136
|View full text |Cite
|
Sign up to set email alerts
|

The effects of long haul transport on pregnant, non-lactating dairy cows

Abstract: Transported cows benefited from overnight rest, feeding and watering in terms of hydration and muscle status, but bodyweight and serum magnesium concentrations were significantly reduced by the overall journey, emphasising the requirement for suitable mineral supplementation and careful feeding and selection of pregnant cows before long-haul transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
3
2
0
Order By: Relevance
“…The glycerol, transported, and betaine groups had lower (P = 0.02) plasma Mg concentration than the control group at 24 h. However, at 48 h the control group had greater (P = 0.05) plasma Mg concentrations compared with the transported group only. The betaine and glycerol groups maintained plasma Mg concentrations between 24 and 48 h. The effect of transportation on cattle plasma Mg concentrations was similar to other studies where a decrease in the plasma Mg concentration of the animal has been recorded (Fisher et al, 1999).…”
Section: Plasma Electrolytessupporting
confidence: 87%
See 1 more Smart Citation
“…The glycerol, transported, and betaine groups had lower (P = 0.02) plasma Mg concentration than the control group at 24 h. However, at 48 h the control group had greater (P = 0.05) plasma Mg concentrations compared with the transported group only. The betaine and glycerol groups maintained plasma Mg concentrations between 24 and 48 h. The effect of transportation on cattle plasma Mg concentrations was similar to other studies where a decrease in the plasma Mg concentration of the animal has been recorded (Fisher et al, 1999).…”
Section: Plasma Electrolytessupporting
confidence: 87%
“…A time effect for all treatment groups demonstrated a decrease in BW with increased time off feed and water. Loss of BW is similar to other reported values in long haul transportation studies (Camp et al, 1981;Fisher et al, 1999). Loss of BW from fasting and transport largely reflect changes in gut fill and defecation and urination rates (Wythes et al, 1980).…”
Section: Body Weightsupporting
confidence: 85%
“…All rhinoceroses, regardless of being fed or not, experienced a decrease in serum calcium, phosphorus, potassium and magnesium concentrations and an increase in total bilirubin concentrations; changes which are usually attributed to a decreased food intake (Muñoz et al 2010). Changes similar to those observed in this study have been documented after periods of fasting in domestic animal species such as equids and cattle (Baetz 1976;Fisher et al 1999;Fisher et al 2009;Muñoz et al 2010). Although within normal reference intervals (Mathebula et al 2012;Hooijberg et al 2017), calcium concentrations decreased and urea concentrations increased more in the nonfed rhinoceroses.…”
Section: Discussionsupporting
confidence: 75%
“…We (Lay et al, 1996) and others (Lambooy and Hulsegge, 1988;Fisher et al, 1999;Merrill et al, 2010) previously demonstrated pregnant cattle were affected by transportation, as evidenced by changes in body weight, percent shrink, and circulating concentrations of cortisol, glucose, minerals, and pregnancy rate. As none of these reports took season of transport or animal temperament into consideration, we investigated if the temperament of pregnant Brahman cattle affected their responses to transportation.…”
Section: Introductionmentioning
confidence: 60%